Alternate row mulching optimizes soil temperature and water conditions and improves groundnut yield in rainfed farming: Alternate row mulching optimizes soil temperature and water conditions and improves groundnut yield in rainfed farming - B S YENAGI,; ROHINI SUGANDHI,; D T KALLESH, (Journal of Oilseeds Research, 2023)
Half mulching coverage within alternate rows (HM) increased soil temperature in the early growth stage and prolonged time of warming compared with full mulching coverage within all rows (FM). Moreover, the magnitude of the warming effect in the early stages under mulching conditions was greater than that of cooling effect in the late stages.